1987
DOI: 10.1037/0021-843x.96.3.280
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the role of eating disturbance from depression in the sex role self-perceptions of anorexic and bulimic inpatients.

Abstract: Previous research has linked specific sex role self-perceptions to two major eating disorders: anorexia nervosa and bulimia. To date, however, sex role self-perceptions and ideals unique to eating disturbance have not been distinguished from those related to depression and other concomitant psychopathology. The Bern Sex-Role Inventory was administered twice (self-ratings and ideal self-ratings) to 83 women: 37 eating disorder inpatients, 12 depressed inpatients, and 34 high school and college students. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Although Pettinati et al (1987) found no relationship between masculinity and eating disorders, they did find that lower masculinity was associated with increased depression. Possibly, eating behavior is affected by masculinity through that indirect relationship.…”
Section: Masculinitymentioning
confidence: 68%
See 1 more Smart Citation
“…Although Pettinati et al (1987) found no relationship between masculinity and eating disorders, they did find that lower masculinity was associated with increased depression. Possibly, eating behavior is affected by masculinity through that indirect relationship.…”
Section: Masculinitymentioning
confidence: 68%
“…The findings, nevertheless, do not always hold. Some investigators have found that although women with eating disorders rate femininity as a higher ideal than those without eating disorders do, they did not differ with regard to actual self-descriptions of their own level of femininity (Pettinati, Franks, Wade, & Kogan, 1987). Infact, some studies have reported either no relationship between femininity and eating behavior (Timko, Striegel-Moore, Sil- & Rodin, 1987) or equal levels of endorsed femininity for women with and without eating disorders (Sitnick & Katz, 1984).…”
Section: Femininitymentioning
confidence: 96%
“…Most researchers tend to agree that high levels of femininity make women more at risk for disordered eating (e.g., Bekker & Boselie, 2002;Steiger et al, 1989;Thornton et al, 1991). However, research on the influence of masculine gender roles on disordered eating in women is more controversial, with some research reporting a relation between high masculine gender roles (or masculine gender role stress) and disordered eating (Bekker & Boselie; Thornton et al) and other studies finding no such relation (Pettinati et al, 1987;Sitnick & Katz, 1984;Steiger et al;Williams & Ricciardelli, 2001). …”
Section: The Present Studymentioning
confidence: 94%
“…However, Williams and Ricciardelli (2001) reported that female college students who displayed symptoms of disordered eating on the Eating Disorders Inventory showed more negative and positive feminine traits on the Australian Sex Roles Scale, but there was no relation between disordered eating and masculine traits. Similarly, Steiger, Fraenkel, and Leichner (1989) found that eating disordered women tended to show hyper-feminine gender role identifications and an absence of masculine gender role traits on the Bem Sex Role Inventory (see also Pettinati, Franks, Wade, & Kogan, 1987;Sitnick & Katz, 1984). Furthermore, Paxton and Sculthorpe (1991) suggested that disordered eating in college women is related to the possession of more negative feminine characteristics, but is also influenced by a perceived discrepancy between current self and having an ideal image of the self that is more masculine in nature.…”
Section: Gender Role Orientation Differences In Disordered Eating Behmentioning
confidence: 99%
“…Indeed, they seem to be increasing in prevalence (Button & Whitehouse, 1981;Schappi, 1985). Most evidence to date on eating disorders suggests that they are linked to multiple factors (Baird & Sights, 1986), many of which have been identified as the following: adherence to gender stereotypes (Belk & Snell, 1989), gender role ideology (Cantelon, Leichner, & Harper, 1986;Pettinatti, Franks, Wade, & Kogan, 1987), family functioning (Waller, Calam, & Slade, 1989), identity and role confusion (Johnson & Maddi, 1985;Striegel-Moore, Silberstein, & Rodin, 1986), sociocultural pressures (Mintz & Betz, 1988), perceptions of control (Harding & Rasic-Lachenmeyer, 1986), pressure to achieve (Cole & Edelmann, 1987;Silverstein, Perdue, Wolf, & Pizzolo, 1988), socioeconomic status (Anderson & Hay, 1985), conservative beliefs (Belk & Snell, 1989;Nasser, 1988) stress (Cattanach & Rodin, 1988), and body image dissatisfaction (Gamer, Garfinkel, Rockert, & Olmsted, 1988).…”
mentioning
confidence: 99%